Bladder Rhabdomyosarcoma in Adolescents at a Tertiary Centre in Indonesia: A Case Series with Focus on Age-Specific Treatment Response and Diagnostic Challenges - Andhyka Brillian Kharisma; Ahmad Zulfan Hendri; Indrawarman Soeroharjo (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Bladder rhabdomyosarcoma (RMS) is a rare type of soft tissue cancer in adolescents, and it often shows up with vague urinary symptoms that can be easy to miss. Compared to younger children, teenagers tend to respond less well to treatment and have lower survival rates, even when given equally intensive therapies. This difference seems to come from both biology and the challenges of diagnosis. We saw two adolescent male patients, aged 17 and 21, who came in with blood in the urine. Imaging with ultrasound and contrast CT scans revealed solid bladder masses with clear hyperenhancement (delta HU 37-38). Pathology and immunohistochemistry (desmin, myogenin, MyoD1) confirmed embryonal RMS, one conventional type and one botryoid variant. Both were staged as pT2bN0M0. Each patient underwent partial cystectomy after an initial TURBT. Neither received chemotherapy. Case 1 had a laparoscopic partial cystectomy in February 2023, while Case 2 had surgery three years earlier. Both were followed closely with cystoscopy every 3-6 months. At 30 and 36 months post-surgery, respectively, both remain disease-free, with normal bladder function and no need for catheters. These cases show that adolescents with localized bladder RMS can do well when the tumor is completely removed, even without chemotherapy. CT hyperenhancement helps raise suspicion, while immunohistochemistry confirms the diagnosis. Partial cystectomy not only achieves complete resection but also preserves bladder function. Ongoing surveillance is critical, and age-specific treatment strategies, focused on surgery plus careful follow-up, deserve further study for this group. Keywords: Rhabdomyosarcoma, Bladder Tumour, Adolescent, Age-Specific Treatment, Diagnostic Delay, Bladder Preservation, Partial Cystectom